2022
DOI: 10.47456/cl.v16i34.38567
|View full text |Cite
|
Sign up to set email alerts
|

Acessando a avaliação social das variantes do onset complexo na variedade carioca

Abstract: Este artigo apresenta os resultados de um estudo que focalizou a percepção das variantes lateral e tepe no onset complexo, como em chiclete ~ chicrete, por ouvintes universitários, moradores da cidade do Rio de Janeiro. O objetivo foi identificar em que medida a forma linguística afeta a percepção de características sociais dos falantes dos estímulos. A hipótese é que a variante tepe será relacionada a perfil socioeconômico baixo, independentemente do sexo dos falantes dos estímulos, e a variante lateral não i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…Cell source is a very effective parameter in the biodistribution of EVs. It is also suggested that EVs from different cell sources demonstrate a high tendency to accumulate in to originated-tissue [63]. On the other hand, a variety of studies reported that intravenously injected EVs show a higher preference to accumulate in mononuclear phagocyte system (MPS) organs like spleen, lung, and liver.…”
Section: Engineered Ev Strategies In Cardiac Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Cell source is a very effective parameter in the biodistribution of EVs. It is also suggested that EVs from different cell sources demonstrate a high tendency to accumulate in to originated-tissue [63]. On the other hand, a variety of studies reported that intravenously injected EVs show a higher preference to accumulate in mononuclear phagocyte system (MPS) organs like spleen, lung, and liver.…”
Section: Engineered Ev Strategies In Cardiac Therapymentioning
confidence: 99%
“…Through changing protein, lipid, and especially miRNA material of EV after isolation, we could lead the targeting and delivery regardless of their cell of origin. There are different loading strategies that are approaching such as electro-poration, heat-shock/ freeze-thaw procedures, sonication, or passive loading methods like incubating the EVs with interested drugs, or molecules [63].…”
Section: Engineered Ev Strategies In Cardiac Therapymentioning
confidence: 99%